Critical approaches to fiction - Shiv K. Kumar (Atlantic Publishers, 2014)
Critical Approaches to Fiction is designed to offer the post-graduate student, and the general reader, a comprehensive cross-section of some of the best critical material available on the theory and practice of fiction. Within the compass of this Volume, the authors have included representative essays by such eminent critics and writers as Saul Bellow, Eudora Welty, Mark Schorer, Philip Rahv and Wayne C. Booth. This book covers, every significant aspect of fiction—plot, character, language, theme, setting and the diverse modes of presentation. It is earnestly hoped that this book would be found eminently useful both by teachers and students of Indian Universities.